La aplicación de prisión domiciliaria en casos de padres con niños menores de cinco años a su cargo - Becerra, Sol (2013)
This work analyzes the house arrest rules in cases of mothers of children\nunder five years old and their application in practice. An analysis is carried out under\nthe perspective of the principle of the best interests of the child, which leads to assert\nthe need for an extensive application of such rules to cases of men in analogous situations\nnot currently legislated. Moreover, the issue is considered from a theoretical-normative\napproach, typical of the sociology of law. A qualitative methodology is employed,\nunder which interviews are conducted with academics and different operators of\nthe Argentine criminal legal system, as well as a jurisprudence survey of the National\nChamber for Cassation in Criminal Matters. A lack of concordance is found between\nthe practice and the regulatory principles relating to the matter under analysis, showing deficits in the existing regulatory framework and the need for greater involvement of\nstate policies.